2018
DOI: 10.2478/environ-2018-0022
|View full text |Cite
|
Sign up to set email alerts
|

Reductions in tree-ring widths of silver fir (Abies alba Mill.) as an indicator of air pollution in southern Poland

Abstract: The aim of the study was to investigate how the emission of pollutants to the atmosphere from the late 19th century until modern times has been recorded in rings of silver fir trees growing in southern Poland. Samples were collected from 24 firs growing in the Beskid Niski Mountains (Western Carpathians). Using a Pressler borer, a single core was collected from each tree. Within the samples, tree-ring widths were measured. On this basis, reductions of tree-ring widths were calculated and subsequently divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
(10 reference statements)
0
6
0
2
Order By: Relevance
“…Compared to other tree species, the relatively high phenotypic resilience of silver fir to changing climate conditions is experimentally proven, although mostly for juvenile trees [12,36,37]; however, silver fir is sensitive to additional negative biotic and abiotic environmental influences, e.g. to industrial air pollution [39]. In the absence of game browsing and industrial air pollution, the species is capable of regenerating vigorously, even outside its historic distribution limits, even in the broadleaved forest zone (Figure 8).…”
Section: Comparison Of Climate Sensitivity Of Silver Fir and Euro-mediterranean Fir Provenancesmentioning
confidence: 99%
“…Compared to other tree species, the relatively high phenotypic resilience of silver fir to changing climate conditions is experimentally proven, although mostly for juvenile trees [12,36,37]; however, silver fir is sensitive to additional negative biotic and abiotic environmental influences, e.g. to industrial air pollution [39]. In the absence of game browsing and industrial air pollution, the species is capable of regenerating vigorously, even outside its historic distribution limits, even in the broadleaved forest zone (Figure 8).…”
Section: Comparison Of Climate Sensitivity Of Silver Fir and Euro-mediterranean Fir Provenancesmentioning
confidence: 99%
“…После введения в начале 1990-х гг. безвредных для окружающей среды технологий, уровни загрязнения воздуха уменьшились и произошло резкое восстановление радиального прироста [63,70,74,82,100,[104][105]112].…”
Section: влияние техногенеза на дендрохронологические параметры древесных растенийunclassified
“…Анализ публикаций показывает, что как правило наблюдается однозначное уменьшение величины радиального прироста древесных видов в ответ на промышленное загрязнение [3, 8, 16, 24, 34, 36, 39, 44-45, 48-49, 56, 63, 70, 74, 80, 82, 95-96, 100, 102, 104-105, 107, 112-113], потеря его чувствительности к климатическим сигналам [3,34,50,[104][105], перераспределение долей ранней и поздней древесины в общем приросте [6, 14, 36-37, 39, 51, 106], изменение длительности онтогенетических периодов и нарушение его цикличности [3,40,[49][50], появление повышенного количества ложных годичных колец или их выпадение [25,34,43,63], ускоренное начало старения древостоев [24,50], зависимость величины прироста от расстояния между древостоями и источниками эмиссии и от ландшафта местности [36,39,63,70,96,102,[104][105], а также тесная связь между уменьшением ширины древесных колец и содержанием в годичных кольцах металлов и различных микроэлементов [38,44,96,107], восстановление прироста после снижения объемов выбросов загрязняющих веществ [9,56,63,70,82,95,[104][105]108].…”
Section: заключениеunclassified
“…A retrospective analysis of annual ring widths and other tree-ring parameters (e.g., chemical composition of the wood, stable isotopes) makes it possible to obtain information on the state of the environment at a high time resolution. Hence, tree rings are often used to assess the long-term effects of air pollution in the environment [29][30][31][32][33][34][35][36][37][38]. These studies have indicated that trees growing in a polluted environment have narrower increments or, in extreme cases, do not produce any increments in a given year [36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, tree rings are often used to assess the long-term effects of air pollution in the environment [29][30][31][32][33][34][35][36][37][38]. These studies have indicated that trees growing in a polluted environment have narrower increments or, in extreme cases, do not produce any increments in a given year [36][37][38].…”
Section: Introductionmentioning
confidence: 99%